The Role of Social Capital in Improving Local Sanitation: A Case Study of Bahbul Village, Kertaraharja, Sobang, Pandeglang, Banten Province - Neneng Fitri Fitriyah; Robert Markus Zaka Lawang (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Proper sanitation is a key indicator of public well-being and aligns with the Community-Led Total Sanitation (CLTS) program. This program aims to change hygienic and sanitary behaviors through community empowerment, utilizing a triggering method to ensure every individual and community has access to basic sanitation, ultimately realizing a community free from open defecation. This study employs a social capital framework, encompassing networks, trust, values, and norms, to analyze and derive lessons from the development of social capital in enhancing CLTS through the Latrine Arisan Program in Bahbul Village, Sobang District, Pandeglang Regency, Banten Province, using a descriptive qualitative approach. The results indicate that trust, networks, values, and norms key elements of social capital are crucial in the implementation of CLTS. Trust among participants in the latrine arisan (savings group) is demonstrated through mutual cooperation in forming groups, electing group leaders, and pooling money for latrines. Social networks among participants and program facilitators from LAZ Harfa are strong and supportive. Values and norms such as consistent saving, avoiding conflicts over clean water, mutual cooperation in building latrines, and adhering to program instructions are well established among the participants.